A CFD-based study on the heat transfer characteristics between the human body and the environment under low-temperature attire - Yu, Shen; Xie, Xiaojun; Guo, Yan; Wang, Jizhe (Frontiers in Bioengineering and Biotechnology, 2025)
In order to study the interaction between the human body, clothing, and environment in a low-temperature environment, a three-dimensional human thermoregulation model was established based on real human body scanning images. The human body was divided into 12 parts by dividing the body into core, equivalent, skin, and clothing layers. Further computational fluid mechanics (CFD) numerical simulation was carried out to realize the measurement and calculation of human physiological parameters, such as human skin temperature, core temperature, and average temperature of the garment surface, in a low-temperature environment. The clothing surface heat transfer, clothing surface average temperature, human skin surface heat transfer, and local skin temperature change rule were explored with the external environmental temperature to establish a basis for the study of the human body’s heat transfer characteristics in a low-temperature environment. To verify the accuracy of the developed numerical model of the human body, the simulated values of the human body model were compared with the experimental measurements of the human local skin temperature and the simulated values in the literature. The results show that the maximum relative error between the local skin temperature of the human numerical model and the experimental measurements of the human body is 3.43%, and the human numerical model has a high degree of accuracy.